Promoters responsive to DNA bending: a common theme in prokaryotic gene expression. - Pérez-Martín, J (1994)
The early notion of DNA as a passive target for regulatory proteins has given way to the realization that higher-order DNA structures and DNA-protein complexes are at the basis of many molecular processes, including control of promoter activity. Protein binding may direct the bending of an otherwise linear DNA, exacerbate the angle of an intrinsic bend, or assist the directional flexibility of certain sequences within prokaryotic promoters. The important, sometimes essential role of intrinsic or protein-induced DNA bending in transcriptional regulation has become evident in virtually every system examined. As discussed throughout this article, not every function of DNA bends is understood, but their presence has been detected in a wide variety of bacterial promoters subjected to positive or negative control. Nonlinear DNA structures facilitate and even determine proximal and distal DNA-protein and protein-protein contacts involved in the various steps leading to transcription initiation.